Disorder to order: how halide mixing in MAPbI3−xBrx perovskites restricts MA dynamics. Issue 9 (8th February 2023) - Fykouras, Kostas; Lahnsteiner, Jonathan; Leupold, Nico; Tinnemans, Paul; Moos, Ralf; Panzer, Fabian; de Wijs, Gilles A.; Bokdam, Menno; Grüninger, Helen; Kentgens, Arno P. M.
Abstract : This work reveals the correlation between anisotropy in MA + reorientation dynamics and the nearest-neighbour halide layout, which is associated with the composition in mixed lead halide MAPbI3− x Br x perovskites. Abstract : Mixed-halide lead perovskites are of particular interest for the design of tandem solar cells currently reaching record efficiencies. While halide phase segregation upon illumination of mixed perovskites is extensively studied, the effect of halide disorder on A cation dynamics is not well understood, despite its importance for charge carrier diffusion and lifetime. Here, we study the methylammonium (MA) reorientational dynamics in mixed halide MAPbI3− x Br x perovskites by a combined approach of experimental solid-state NMR spectroscopy and molecular dynamics (MD) simulations based on machine-learning force-fields (MLFF). 207 Pb NMR spectra indicate the halides are randomly distributed over their lattice positions, whereas PXRD measurements show that all mixed MAPbI3− x Br x samples are cubic. The experimental 14 N spectra and 1 H double-quantum (DQ) NMR data reveal anisotropic MA reorientations depending on the halide composition and thus associated disorder in the inorganic sublattice. MD calculations allow us to correlate these experimental results to restrictions of MA dynamics due to preferred MA orientations in their local Pb8 I12− n Br n "cages". Based on the experimental and simulated results, we develop a phenomenological model that correlates the 1 H dipolar coupling and thus the MA dynamics with the local composition and reproduces the experimental data over the whole composition range. We show that the dominant interaction between the MA cations and the Pb–X lattice that influences the cation dynamics is the local electrostatic potential being inhomogeneous in mixed halide systems. As such, we generate a fundamental understanding of the predominant interaction between the MA cations and the inorganic sublattice, as well as MA dynamics in asymmetric halide coordinations.